2004
DOI: 10.1002/jsfa.1631
|View full text |Cite
|
Sign up to set email alerts
|

Changes in carotenoids and chlorophylls in fresh green asparagus (Asparagus officinalis L) stored under modified atmosphere packaging

Abstract: Asparagus is a highly perishable product owing to its high respiratory rate, a reason why modified atmosphere packaging (MAP) has been used in order to increase the shelf-life of fresh asparagus. Carotenoid and chlorophyll pigments are important compounds for the maintenance of both the nutritional and sensory quality of asparagus. In this study, green asparagus spears were stored under refrigeration at 2 • C for 14 days, under MAP at 2 • C for 26-33 days and under MAP at 10 • C for 20 days. Pigment profiles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 21 publications
2
13
0
1
Order By: Relevance
“…As expected, differences in chlorophyll a and b concentrations between fresh and cooked vegetables were found to be statistically significant (P < 0.05). More chlorophyll a was extracted than chlorophyll b in all fresh samples and was more labile than chlorophyll b owing to its greater susceptibility to pheophytinization during heating as it has been already reported in earlier studies (Lo´pez-Ayerra et al, 1998;Tan et al, 2000;Tenorio et al, 2004). As an example, the HPLC chromatogram of chlorophylls and their derivatives obtained for fresh and microwaved broccoli is shown in Fig.…”
Section: Chlorophylls and Derivativessupporting
confidence: 53%
“…As expected, differences in chlorophyll a and b concentrations between fresh and cooked vegetables were found to be statistically significant (P < 0.05). More chlorophyll a was extracted than chlorophyll b in all fresh samples and was more labile than chlorophyll b owing to its greater susceptibility to pheophytinization during heating as it has been already reported in earlier studies (Lo´pez-Ayerra et al, 1998;Tan et al, 2000;Tenorio et al, 2004). As an example, the HPLC chromatogram of chlorophylls and their derivatives obtained for fresh and microwaved broccoli is shown in Fig.…”
Section: Chlorophylls and Derivativessupporting
confidence: 53%
“…Although there is little previous data on carotenoids in edible shoots, there are some data for commercial asparagus ( A. officinalis ), which, in general, show lower carotenoid contents than those obtained in this study . A higher content of neoxanthin compared with β ‐carotene was reported by Tenorio et al ., a finding that is in agreement with the present profile obtained for A. acutifolius , B. dioica and T. communis . Data reported by USDA for β ‐carotene content in commercially available asparagus (49.3 mg g −1 wet weight) are very close to the β ‐carotene in this study.…”
Section: Resultssupporting
confidence: 92%
“…Neoxanthin acts as an inhibitor of chemically induced carcinogenesis and is involved in reducing the viability of prostate cancer cells . Although the presence of both neoxanthin and violaxanthin has been reported in green vegetables they are not often included in food composition databases (with some exceptions, such as the Brazilian food composition database, which includes violaxanthin) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorophyll loss is reduced in vegetables stored at higher CO 2 levels (Shewfelt, Batal, & Heaton, ). Several studies have found that the total chlorophyll content of leafy greens, including broccoli, chives, garden peas, and asparagus, is better retained at low and relatively high levels of CO 2 (Imahori et al., ; Jamie & Saltveit, ; Pariasca, Miyazaki, Hisaka, Nakagawa, & Sato, ; Tenorio, Villanueva, & Sagardoy, ). Thus, the ambient atmosphere inhibits chlorophyllase and/or peroxidase activities, reducing chlorophyll degradation.…”
Section: Resultsmentioning
confidence: 99%